Husein Muhammad's Thoughts on Husband's Iddah and His Contribution to the Development of Family Law in Indonesia - Rofi'i, Hilmi Yusron (Universitas Islam Negeri Raden Intan Lampung, 2023)
This article discusses the thoughts of Husein Muhammad regarding the husband's iddah and his contribution to the development of family law in Indonesia. this article uses a qualitative method, analyzing in depth about the thoughts of Husein Muhammad, related to the iddah period of the husband, this article is a library research or literature study, by studying the literature of Husein Muhammad's work on Iddah, the main data source in this study is the work of Husein Muhammad, the data analysis technique uses an inductive framework using mashlahah and mubadalah analysis. The result of the research is that Husein Muhammad's thinking leads to a more inclusive, progressive, humanist and contextual understanding of family law and is adaptive to the dynamics of Indonesian society which continues to develop by detailing the iddah time frame and the rights attached to that period. Husein Muhammad's thinking on iddah has a positive impact on the development of family law in Indonesia, linking its theoretical aspects to concrete changes in the family law system and providing a strong foundation for further change.Keyword: Husein Muhammad, Iddah Period, Husband, Family Law